A study of urinary tract infection in pregnancy and its effect on maternal and perinatal outcome - Kerure, Rajshekhar D.; Biradar, Amaresh V.; Lakshetty, Swetha; Biradar, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Urinary tract infection (UTI) during pregnancy is very common in developing countries like India. UTI is caused by the growth of micro-organisms in the urinary tract. This study aims to determine the incidence of UTI in whole pregnancy and its adverse effects on mother and fetus. Methods: This is a prospective study conducted in outpatient department of ESIC medical college for one year from January 2017 to December 2017. A total of 182 pregnant women attending OBG OPD for ANC check-up without any medical disorders or previous adverse pregnancy outcomes of 18-35 years of age were included in the study. Urine routine and urine culture sensitivity were done for all. Results: Out of 182 pregnant women tested for UTI, the incidence of UTI in pregnancy was found to be 19%. Asymptomatic UTI was noted in 65% patients with UTI. Primigravida were commonly affected (56%). Highest cases were in 18 to 25 years (63%) age group. 56% cases showed 6-10 pus cells/HPF. Prevalence of UTI was more common in winter seasons. Commonest causative organism was E. coli in 38% cases. Maternal complications like anaemia (26%) and puerperal pyrexia (23%) were observed. Adverse fetal outcomes like preterm birth (35%) and fetal growth restriction (15%) were observed. Conclusions: In this study, the prevalence rate of UTI during pregnancy is high (19%). The physiological changes of pregnancy predispose the women to UTI so does the other factors such as age, sexual activity, hygiene, multiparty, previous history of UTI and socio-economic conditions. All pregnant women should be screened for UTI with a urine routine and urine culture, treated with antibiotics if the culture is positive and then retested for cure. Awareness has to be created about good hygienic practices and adequate hydration among pregnant women.